Influência de fatores alimentares no nível sérico de vitamina D e o efeito da hipovitaminose D sobre condições clínica e radiográfica de pacientes com próteses sobre implantes - Verde, Luis Henrique Cerqueira Vila (2017)
Vitamin D (VD) plays an important role in the development and maintenance of bone tissue. At normal levels, it has positive effect on volume, bone quality as well as its density. Considering the large number of people who present serum changes of the same, this research aims to observe the rate of hypovitaminosis D (hD) in the study population and the factors that may influence the incidence of hD, and to evaluate the influence of hD on peri-implant clinical and radiographic conditions. All the participants of the groups were submitted to a Semi-quantitative Food Frequency Questionnaire on the intake of dietary calcium (QFASQ), in order to evaluate the risk factors. Patients were submitted to laboratory tests of 25-hydroxyvitamin D dosing, those with a serum LDL level of less than 30ng / mL were allocated to the abnormal (insufficient or defficient) group and the participants with dosages equal to or greater than 30ng/mL were allocated to the normal (sufficient) group. Participants received the following evaluations: peri-implant clinical analysis (depth of probing, keratinized mucosa width, modified groove bleed index, modified plaque index), radiographic analysis (distance between the implant cervical and the mesial and distal). Patients who were allocated to the abnormal group were submitted to VD replacement, and a new clinical and radiographic analysis was performed. It was found that in the initial study population about 36% of individuals had hD. As for the food questionnaire, lower intake of milk products, such as yogurt and lower frequency of physical activities, showed a higher risk for one hD. Clinical analysis showed that VD was statistically non-statistically significant for probing depth, keratinized mucosal width, modified plaque index, and for modified bleeding index between the 2 periods, in relation to peri-implant parameters. It was concluded that less than half of the sample had hD and calcium-rich foods may contribute to normal serum levels of VD. VD did not influence the peri-implant clinical parameters studied.